Exploring Vegetarian and Omnivorous Approaches to Cardiovascular Risk and Body Composition - Fontes, Tatiana; Lopes, Sofia; Menezes, Regina; Esgalhado, Marta; Monteiro Rodrigues, Luís; Ferreira-Pêgo, Cíntia (Nutrients, 2024)
The role of nutrition in preventing non-communicable diseases has been widely studied in recent years, with indications that non-animal-based diets might improve body composition and therefore bring multiple health benefits. For all of these reasons, the main purpose was to compare body composition and metabolic status between vegetarian and omnivorous individuals and relate these values with cardiovascular risk. The present analysis included 176 participants (61 vegetarians and 115 omnivores). Body composition was assessed using a dual-energy X–ray absorptiometry, biochemical parameters obtained from capillary blood, and the 10-year cardiovascular risk (10RCVD) calculated by the QRISK3 score. No statistical differences were found between groups regarding body composition. Concerning metabolic markers, vegetarian individuals showed reduced values of total cholesterol, LDL cholesterol, and non–HDL cholesterol (p < 0.05). There were no differences in 10RCVD between groups. In both diets, moderate correlations between groups were found for cardiovascular risk and visceral adipose tissue. Our results suggest that the vegetarian regimen might be associated with better cardiometabolic biomarkers and better cardiovascular health, although controversial with the body composition trends observed. In conclusion, the results suggest that cardiovascular risk appears to be more influenced by body composition, mainly fat tissue, over dietary patterns itself.